Page 12 - e-modul turunan fungsi aljabar
P. 12

CONTOH SOAL




                                 3
                3.       = 9   − 3   +         5
                                                 2

                                          3
                                                                           2
                       Misal : u = 9    →  u’ = 9.3.         3−1   = 27  

                                ′
                                               ′
                                 = 3   →    = 3         1−1  = 3



                                        5                                                              −10
                                                            ′
                                 ′
                                 =         = 5    −2  →    = 5 −2 .          −2−1   = −10      −3  =
                                          2                                                                3

                                                                        ′
                                                                                    ′
                                                                                           ′
                                                                                                  ′
                       Jadi, jika       =    −    +   ,                =    −    +   

                                                                              10
                                                    ′
                                                                   2
                                                        = 27   − 3 −
                                                                                 3

                                     2
                4.       = 5   −    + 1
                                         2

                                                ′
                       Misal:    = 5   →    = 5          1−1  = 5




                                                2            2    2       2     1          2
                                     3                  ′          −1          −
                                         2
                                 =        =    →    =              3   =         3  = −
                                                3
                                                                                           3
                                                             3            3              3   
                                              ′
                                 = 1 →    = 0


                                                                                           ′
                              Jadi, jika       =    −    +   ,                =    −    +   
                                                                                ′
                                                                                                  ′
                                                                                                         ′

                                                                   2
                                                 ′
                                                     = 5 −
                                                                   3
                                                                 3   



                                                                                                        12
   7   8   9   10   11   12   13   14   15   16   17